Bulletin 70 A Preliminary Report on Uranium Radium and Vanadium - Richard B. Moore; Karl L. Kithil (The National Institute for Occupational Safety and Health (NIOSH), 1916)
This bulletin presents a summary of available information regarding the sources of uranium, radium, and vanadium, the methods used in treating the ores, and the uses of the finished products. In particu- lar the paper describes the ores found in the United States, giving especial attention to those characteristics of the ores and the conditions of their occurrence that affect mining and treatment.